2017
DOI: 10.1016/j.cell.2017.01.013
|View full text |Cite
|
Sign up to set email alerts
|

Gene Essentiality Profiling Reveals Gene Networks and Synthetic Lethal Interactions with Oncogenic Ras

Abstract: SUMMARY The genetic dependencies of human cancers widely vary. Here, we catalog this heterogeneity and use it to identify functional gene interactions and genotype-dependent liabilities in cancer. By using genome-wide CRISPR-based screens, we generate a gene essentiality dataset across 14 human acute myeloid leukemia (AML) cell lines. Sets of genes with correlated patterns of essentiality across the lines reveal new gene relationships, the essential substrates of enzymes, and the molecular functions of unchara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

37
560
1
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 574 publications
(610 citation statements)
references
References 63 publications
(74 reference statements)
37
560
1
2
Order By: Relevance
“…We and others have observed that cancer cell lines exhibit highly variable genetic dependencies for cellular fitness (Bertomeu et al, 2018; Blomen et al, 2015; Hart et al, 2015; Hart et al, 2017a; McDonald et al, 2017; Meyers et al, 2017; Tsherniak et al, 2017; Wang et al, 2015; Wang et al, 2017b) in a manner that reflects the diverse genomic and transcriptomic alterations a cell may accumulate during tumorigenesis. Project Achilles (Broad Institute of MIT and Harvard) seeks to systematically map genetic vulnerabilities across large collections of cancer cell lines, including the Cancer Cell Line Encyclopedia (CCLE) (Barretina et al, 2012), and has recently performed genome-scale perturbation screens in 501 cancer cell lines using RNA interference (RNAi) (Tsherniak et al, 2017) and in 342 cancer cell lines using CRISPR-Cas9 (Meyers et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…We and others have observed that cancer cell lines exhibit highly variable genetic dependencies for cellular fitness (Bertomeu et al, 2018; Blomen et al, 2015; Hart et al, 2015; Hart et al, 2017a; McDonald et al, 2017; Meyers et al, 2017; Tsherniak et al, 2017; Wang et al, 2015; Wang et al, 2017b) in a manner that reflects the diverse genomic and transcriptomic alterations a cell may accumulate during tumorigenesis. Project Achilles (Broad Institute of MIT and Harvard) seeks to systematically map genetic vulnerabilities across large collections of cancer cell lines, including the Cancer Cell Line Encyclopedia (CCLE) (Barretina et al, 2012), and has recently performed genome-scale perturbation screens in 501 cancer cell lines using RNA interference (RNAi) (Tsherniak et al, 2017) and in 342 cancer cell lines using CRISPR-Cas9 (Meyers et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…ICMT is the only cellular enzyme known to methylate prenylcysteine substrates; methylation is important for their biological functions, including the membrane localisations and subsequent activities of Ras 1 , prelamin A 3 , and Rab 4 . ICMT inhibition has potential for combating progeria 3 and cancer 58 . Here we present an X-ray structure of ICMT, at 2.3 Å resolution, in complex with its cofactor, an ordered lipid molecule and a monobody inhibitor.…”
mentioning
confidence: 99%
“…A recent study indicates that ICMT has a synthetic lethal interaction with oncogenic Ras 8 , suggesting possible efficacy of ICMT inhibitors for Ras-driven cancer. ICMT inhibitors may also have utility in treating progeria, the pathology of which is attributed to the accumulation of a prenylated and methylated form of prelamin A at the nuclear envelope 3,24 .…”
mentioning
confidence: 99%
“…18 Pak kinases, as downstream effectors of Ras, are potential therapeutic targets in malignancies with hyperactive Ras, which account for ;30% of human cancers and are common in myeloid malignancies. [52][53][54][55] However, the reports that Pak2 depletion suppresses b-catenin activity 56 and downregulation of b-catenin promotes human MDSC activation and expansion in cancer 57 raise safety concerns regarding the pharmacological inhibition of group I Paks that target Pak1, Pak2, and Pak3. Our findings provide further evidence that the efficacy of targeting Paks may be undermined by tumor escape from immune control and/or acceleration of tumorigenesis through MDSC expansion.…”
Section: Discussionmentioning
confidence: 99%